EFFECT OF THE IMPLEMENTATION OF KEY PERFORMANCE INDICATOR ON CAREER DEVELOPMENT AT THE ONE LEGIAN - I Made Dede Ardika; I Gusti Agung Bagus Mataram; I Gede Mudana (Politeknik Negeri Bali, 2018)
It is important to always develop a career for all employees for a company including hotel companies, because employees are one of the assets used by companies to achieve corporate goals that have been set previously. The purpose of this study is to determine the effect of key performance indicators applicant to the career development. The ONE Legian is a research location with 55 respondents. Data collection methods used were questionnaires and observations. Data processing techniques that is the test of validity and reliability, and data analysis techniques, namely simple regression and hypothesis testing. The results of the analysis of this study indicate that the implementation of key performance indicators have a significant positive effect on career development. From the results of t test obtained t-count value 6.590> t-table 1.674 with probability 0.000. Because the probability value is much less than 0.05, therefore the key performance indicator variable partially has significant positive effect on career development at The ONE Legian